Prevalence of hypertension in a sample of community members in a low-income peri-urban setting in Gaborone, Botswana - Zelda Janse Van Rensburg; Craig Vincent-Lambert; Radmila Razlog; Ntambi Phaladze (AOSIS, 2023)
Background: Cardiovascular disease remains the leading cause of death worldwide. Hypertension is a primary risk factor for the development of cardiovascular disease and affects more than a quarter of the global adult population. Africa is a continent where the prevalence of non-communicable diseases including cardiovascular disease and hypertension, is increasing rapidly. Botswana is a developing country in Sub-Saharan Africa. In such contexts the early identification of hypertension, through community screening initiatives, is an important tool for the management of cardiovascular disease in the population. Objective: To investigate and describe the prevalence of hypertension in a sample of community members residing in a low-income peri-urban setting in Gaborone, Botswana. Method: 364 adult participants had their blood pressures measured during a community health screening exercise. The values were analysed and categorised using the American Heart Association classification scale as either being normal, elevated, hypertensive stage 1 or hypertensive stage 2. Results: 234/364 (64%) of participants were found to have blood pressures within normal limits. 53/364 (15%) had elevated blood pressures, 57/364 (16%) were in hypertensive stage 1 and 20/364 (5%) were in hypertensive stage 2. Conclusions: Hypertension in Africa is a growing concern. Botswana appears to be no exception with a 36% prevalence of abnormal blood pressures being recorded. However, the majority of these were classified as elevated or stage 1. Early identification and treatment of hypertension in these early stages can significantly decrease the risk of developing stage 2 hypertension and the related systemic complications.